Exploring the maintenance of plumage polymorphism in the Black Sparrowhawk - Tate, Gareth John (Percy FitzPatrick Institute of African Ornithology, 2017)
Animals often display striking variation with respect to their phenotype. Intraspecific and interspecific variation in body colour represents one of the most well studied forms of phenotypic variation. For decades evolutionary biologists have been fascinated by the mechanisms that maintain colour variation in species and traditional explanations for this diversity of colour in nature often invoke an interaction between selection for conspicuous signals and natural selection for crypsis. Colour polymorphic species have frequently been used to explore the evolutionary processes that lead to colour variation in species. Geographic variation in colour morph ratios also occurs frequently in polymorphic species and is often considered an ideal model system to examine the interplay of gene flow and local adaptation in populations. This thesis aims to explore the role and maintenance of plumage colour polymorphism in a raptor, the black sparrowhawk. The black sparrowhawk exhibits discrete colour polymorphism, with adults occurring as either white or dark morphs. Within South Africa, the species has undergone a recent range expansion, successfully colonising the Cape Peninsula in the Western Cape. As winter breeders, black sparrowhawks in South Africa now experience two contrasting climatic regimes; dry winters in their historical north-eastern range, and wet winters in the recently colonised Western Cape region. Within this newly colonised region, the dark morph occurs in greatest frequency. Across South Africa, the species displays clinal variation, with the frequency of dark morphs declining from > 75 % in the far south-west on the Cape Peninsula, to < 20 % in the north-east of the country. Two contrasting hypotheses have been proposed for the high frequency of dark morph birds in the Cape Peninsula population; (1) that colour variation is non-adaptive and is simply due to a chance founder effect and strong genetic drift and (2) this is reflective of local adaptation and that irrespective of the founding morph ratios, dark morphs have a selective advantage in this newly colonised environment with its novel winter rainfall regime. The main aims of this study were to determine the (i) ecological and evolutionary mechanisms that influence the maintenance of colour polymorphism in the species and (ii) to establish explanations for the unusually high proportion of dark morphs on the Cape Peninsula. In this thesis I have used a range of ecological and genetic approaches to explore both neutral and adaptationist explanations for the high frequency of dark morphs in my study population. Data from the mitochondrial control region was used to examine the distribution of genetic diversity in several geographic populations of black sparrowhawks across South Africa, allowing the exploration of trait divergence under neutrality. Using a phylogeographic framework, genetic variation was used to (i) quantify the extent to which population structure and gene flow may influence the observed pattern of colour morphs in the focal study population on the Cape Peninsula, and (ii) explore how selection and gene flow may interact to explain the patterns of morph frequencies in my study system. I found very low genetic differentiation between sample sites across South Africa suggesting that substantial gene flow occurs among populations, supporting the hypothesis that selection, and thus local adaptation, is the primary force maintaining colour variation on the Peninsula.